Transformasi Peran Agama Dalam Mengarahkan Perubahan Sosial Melalui Media Digital: Transformation of the Role of Religion in Guiding Social Ethics in Society through Digital Media - Wasilatul Jariah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
Globalization has brought about transformations in society, particularly in the context of life in the digital era. This change has caused a significant shift, where the role of religion undergoes adjustments in response to the impacts of modern advancements. In the digital era, the dissemination of religious values is no longer limited to institutions or religious education centers but also occurs through various digital platforms such as social media, websites, and applications. This study aims to explore how the role of Islam shifts from a conventional approach to a digital approach and how digital media functions as a strategic tool in guiding social transformation. The research employs a descriptive qualitative approach, using a library research method to review literature and previous studies related to religion, digital media, and social change. The findings indicate that digitalization presents opportunities for religion to expand the reach of preaching and religious education through digital media, but it also poses challenges in the form of unverified information and a decline in understanding of moral values. Therefore, strengthening religious digital literacy is necessary so that digital media can be effectively utilized to support the development of a religious culture and constructive social interaction.